Efficacy and Safety of Hylan G-F 20 Versus Intra-Articular Corticosteroids in People with Knee Osteoarthritis: A Systematic Review and Network Meta-Analysis. Issue 13 (November 2020) - Chevalier, Xavier; Sheehan, Brendan; Whittington, Craig; Pourrahmat, Mir-Masoud; Duarte, Lionel; Ngai, Wilson; de Campos, Gustavo Constantino
Background: Direct injection of corticosteroids into the joint is a standard treatment for knee osteoarthritis (OA). However, the treatment is somewhat controversial with regard to the benefit of both single and repeated injections; evidence that they are beneficial comes from small studies that show only modest improvements. The aim of this study was to estimate the short- and long-term clinical efficacy and safety of hylan G-F 20 versus intra-articular corticosteroids (IACS) for the treatment of pain in knee OA using Bayesian network meta-analysis. Methods: Based on a pre-specified protocol, MEDLINE, Embase, and CENTRAL were searched from inception to June 2018 to identify randomized controlled trials. The Cochrane Collaboration's tool for assessing risk of bias in randomized trials was used to assess the included studies. Hylan G-F 20 and IACS were compared using Bayesian network meta-analysis. Efficacy was evaluated at 1, 3, and 6 months, and at the final follow-up for safety outcomes. A pain hierarchy was used to select 1 pain outcome per study. Results: Forty-two trials were included for analysis. The network meta-analysis of pain showed that hylan G-F 20 may be equivalent to IACS in the short-term, but by 6 months the benefit relative to IACS was statistically significant, standardized mean difference (95% credible interval): –0.13 (–0.26, –0.01). There were no statistical differences in adverse events. Conclusions: Hylan G-F 20 may perform better in relieving pain at 6 months post-injection compared to IACS. Both agents were relatively well tolerated, with no clear differences in safety.